9-7(y+6)=-3(y+5)

Simple and best practice solution for 9-7(y+6)=-3(y+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9-7(y+6)=-3(y+5) equation:



9-7(y+6)=-3(y+5)
We move all terms to the left:
9-7(y+6)-(-3(y+5))=0
We multiply parentheses
-7y-(-3(y+5))-42+9=0
We calculate terms in parentheses: -(-3(y+5)), so:
-3(y+5)
We multiply parentheses
-3y-15
Back to the equation:
-(-3y-15)
We add all the numbers together, and all the variables
-7y-(-3y-15)-33=0
We get rid of parentheses
-7y+3y+15-33=0
We add all the numbers together, and all the variables
-4y-18=0
We move all terms containing y to the left, all other terms to the right
-4y=18
y=18/-4
y=-4+1/2

See similar equations:

| (x+2)(x+5)=3x+7 | | 100p=1100-(p+) | | 3×n/20=48/80 | | 1/4X^2-4x+7=0 | | 61-4x=3x+12 | | 7x-2=10x-47 | | 2/7x+3/7=5 | | 6(1)-4x=3x+12 | | X2+4x+3=0 | | (x-5)^2-(2x-7)=8(8-x) | | -105=-7(1+2n | | -3x+3=-2x-1 | | X2-4x+3=0 | | d-4/2=3 | | N^2+20n+99=0 | | 5x-2(3x-8)=14 | | 4(x-6)-3(x-8)=30 | | Y=4+8x-2x^2 | | 72=​2​​m​​−7 | | F(x)=1/x+25 | | 533/x=41 | | 43x=1118 | | 1935÷x=45 | | -6(2+3v)=123 | | X2-x-30=0 | | 10*10=x*10 | | 39×x=780 | | -6x+7=4x/25 | | 86-x=50 | | 67-x=32 | | 37x=1221 | | 6(3-2y)=9+2y |

Equations solver categories